Pathophysiological insights and therapeutic developments in age-related hearing loss: a narrative review - Sun, Shichu; Zhao, Qi; He, Haojia; Liu, Yujia; Nie, Yuchong; Zhou, You (Frontiers in Aging Neuroscience, 2025)
Age-related hearing loss (ARHL), or presbycusis, is characterized by a progressive decline in binaural auditory sensitivity, particularly affecting high-frequency hearing and sound localization. The pathogenesis of ARHL is still unclear, correspondingly reflected in a lack of clinically effective intervention strategies. Recent advancements in audiology and neurobiology have illuminated the black box of the pathogenesis of ARHL. The intricate mechanisms underlying ARHL involve inflammation, oxidative stress, excessive autophagy, cellular signaling dysregulation, and metabolic alterations, which cause substantial damage to cellular function within cochlea. The weakened sound conduction and reduced auditory information processing potentially lead to emotional distress and heightened susceptibility to neurodegenerative conditions like cognitive decline and dementia. Promising interventions targeting these mechanisms are actively being investigated, ranging from pharmacological approaches to genetic therapies and lifestyle interventions. This narrative review summarizes recent research progress in understanding ARHL pathogenesis and discusses emerging strategies for prevention and treatment, highlighting the imperative for targeted interventions to enhance auditory health and overall well-being in aging populations.